METODE TAHFIZH AL-QUR'AN DI PONDOK PESANTREN MUHAMMADIYAH BOARDING SCHOOL KLATEN - Meti Fatimah (Institut Islam Mamba'ul 'Ulum Surakarta, 2020)
Until now, memorization is still one of the methods used in the process of maintaining the Koran. This research is related to the tahfizh al-Qur'an method which is more directed at the learning process at the Muhammadiyah Boarding School Klaten Islamic boarding school. The research aims to reveal descriptively the methods of learning khifdhul jaded and khifdhul coding in improving the quality and quantity of memorizing al-Qur'an of the students of the boarding school Muhammadiyah boarding school Klaten. This qualitative research is a research approach that produces descriptive data, which is written or oral data and observe people's behavior. The research data collection was carried out by means of observation, interviews, and documentation. Data analysis is a process of organizing data into patterns, categories and a basic description, so that a working hypothesis can be found and formulated. The first stage is data reduction, the second stage is a data exploration and the third stage is data verification. The results showed that tahfizh al-Qur'an at the Muhammadiyah Boarding School Klaten Islamic boarding school used the khifdhul jaded and khifdhul coding methods to memorize al- Qur'an. The khifdhul jaded method and the khfidhul coding method applied at the boarding school Muhammadiyah boarding school Klaten should be more focused so that it is more effective so that every year not only ten students who memorize the Koran will pass but more and more will pass the al-Qur'an memorizer. 'An. The khifdhul jaded method and the khfidhul coding method applied at the boarding school Muhammadiyah boarding school Klaten should be more focused so that it is more effective so that every year not only ten students who memorize the Koran will pass but more and more will pass the al-Qur'an memorizer. 'An. The concept of memorizing the Koran by using the khifdhul jaded method and the khifdhul coding method applied at the boarding school Muhammadiyah boarding school Klaten must be a rote method that will produce memorizers of the Koran with good memorization quality, according to the correct rules. Both in terms of the letter makharijul, recitation and from the way of reading it in a beautiful voice.